A Rebel by Any Other Name: The Onomastics of Disney's Star Wars Rebels - Allen, Spencer L. (Journal of religion and popular culture, 2019)
Set five years before Episode IV: A New Hope, Star Wars Rebels (2014-18) is an animated series focused on a band of smugglers who join the Rebel Alliance. In keeping with Lucas's Star Wars universe, Star Wars Rebels's two Jedi characters have biblical names: Jedi Kanan Jarrus (also known as Caleb Dume) and his Padawan, Ezra Bridger. Additionally, other main characters include myth-named aliens Hera and Janus and Roman-named humans with Imperial links, such as Rex, Sabine, Tiber, Titus, and Konstantine. This article explores the meanings of these names for their characters and their implications in the larger struggle between the Rebel Alliance and the Galactic Empire.